Chronicles of conflicting care in confinement: Documenting the work experiences of seven 'patient zeros'. Issue 2 (11th September 2020) - van Eck, Dide; Jammaers, Eline
Abstract : This article documents the experiences of a group of working women who were amongst the first diagnosed with COVID‐19 in their country. Through interviews at two points in time, personal diaries and WhatsApp conversations, we lay bare how feelings of shame, hate and guilt for being patient zeros intersect with the experience of intensified care work during the lockdown. Care during the confinement became a central feature of everyday life and often took a virtual turn, both among families and friends as well as in the distanced workplace. Yet meaningful caregiving from the organizations in times of economic uncertainty was mostly lacking and passed on to individual employees who felt a moral and gendered obligation to substitute for the corporate carelessness. The conflicts of care that emerged out of this situation came at the cost of self‐care. We argue that, although the women in our study are mostly privileged, there is a surprising amount of suffering that took place. Finally, we question our own care ethics as researchers in further burdening those suffering in pandemic times to participate in this study.